Joy operations - Bendis, Brian Michael (Dark Horse Books, 2022)
"Fifty-five years from now. Joy is an En·Voi. A special agent of one of the Jonando Trust. Trusts are corporate-owned cities that are the centerpiece of modern society. She rights wrongs for the trust. She is excellent. Perfection. Hard on herself. Driven. Almost legendary in some parts. Until one day a voice pops in her head trying to get her to betray everything she has ever believed. This meticulously-designed Akira meets Inception journey shows us a new future like only comics can. All this and also an exclusive look behind-the-scenes and a look forward to other Jinxworld projects coming exclusively to Dark Horse."--